Anesthetic Effect of the Fascia Iliaca Compartment Block with Different Approaches on Total Hip Arthroplasty and Its Effect on Postoperative Cognitive Dysfunction and Inflammation - Feng, Tengchen; Zhao, Jibo; Wang, Jiayi; Sun, Xiaojia; Jia, Tong; Li, Fulong (Frontiers in Surgery, 2022)
Objective The objective of this article is to make a comparison of the anesthetic effects of the inside and outside fascia iliaca compartment block (FICB) in total hip arthroplasty (THA) and to study the effect of the different approaches of the FICB on postoperative cognitive dysfunction (POCD) and serum inflammatory cytokines in THA patients. Methods A total of 60 patients who received THA treatment from January 2021 to December 2021 were divided into two groups, namely, Inside group (inside approach of the FICB) and Outside group (outside approach of the FICB), according to the different approaches of the FICB. Forty-eight hours after surgery, we compared the use of ropacaine dosage, visual analogue scale (VAS) score, the use of patient-controlled analgesia (PCA), mini-mental state examination (MMSE) score, the incidence of POCD, and the serum levels of IL-1, IL-6. Secondary indicators include surgical indicators and the quality of anesthesia cannula. Results The ratio of re-fix the catheter, intubation time, and the use of ropacaine dosage at 48 h after surgery in the Outside group were significantly higher than that in the Inside group (p < 0.05), while the depth of cannulation in the Outside group was significantly lower than that in the Inside group (p < 0.05). VAS scores were comparable between the Inside and the Outside groups, except at 24 h after surgery. The use of PCA from 24 to 48 h after surgery in the Outside group was significantly higher than that in the Inside group (p < 0.05). The MMSE score and the incidence of POCD in the Outside group were higher than that in the Inside group. At the same time, the serum IL-1β levels at 1 and 6 h after surgery and the serum IL-6 levels at 1, 6, 24, and 48 h after surgery in the Outside group were significantly higher than that in the Inside group (p < 0.05). Conclusion Compared with the outside approach of the FICB, the inside approach of the FICB has better anesthetic effect, better postoperative analgesia, fewer postoperative analgesics, lower incidence of POCD, and lower serum cytokines during the treatment of THA patients.